Overcoming interface losses in organic solar cells by applying low temperature, solution processed aluminum-doped zinc oxide electron extraction layers - Stubhan, Tobias; Litzov, Ivan; Li, Ning; Salinas Batallas, Michael; Steidl, Matthias; Sauer, Gerhard; Forberich, Karen; Matt, Gebhard; Halik, Marcus; Brabec, Christoph (Journal of Materials Chemistry A, 2013)
Intrinsic zinc oxide (ZnO) is widely used as an electron extraction layer (EEL) for inverted polymer solar cells. Despite the excellent device performance, a major drawback for large area production is its low conductivity. Using microscopic simulations, we derived a technically reasonable threshold value of 10−3 S cm−1 for the conductivity required to overcome transport limitations. For conductivity values typical for ZnO we observed the interface layer thickness restriction at only a few tens of nanometers, either as a fill factor drop due to serial resistance, eventually accompanied by a second diode behavior, or by the need for light soaking. Higher conductive aluminum-doped zinc oxide (AZO), which was introduced earlier, meets the desired conductivity threshold, however, at the cost of high temperature processing. High annealing temperatures (>150 °C) significantly improve the electrical properties of ZnO, but prohibit processing on plastic substrates or organic active layers. Here we report on AZO layers from a sol–gel precursor, which has been already reported to give sufficiently high conductivities at lower processing temperatures (<150 °C). We investigate the influence of different precursor compositions on the electrical properties of the thin films and their performance in inverted poly(3-hexylthiophene):[6,6]-phenyl-C61-butyric acid methyl ester (P3HT:PCBM) solar cells. Low temperature AZO layers with thicknesses up to 680 nm maintained comparable performance to devices with thin AZO layers.
Keywords: Aluminum-doped zinc oxide; Annealing temperatures; High-temperature processing; Inverted polymer solar cells; Microscopic simulation; Organic active layers; Poly (3-hexylthiophene); Processing temperature Engineering controlled terms: Aluminum; Electric properties; Extraction; Processing; Sol-gels; Solar cells; Temperature Engineering main heading: Zinc oxide